Perrotta-Marciano Burnout Risk Interview 1 (BORI-1): The new clinical interview to investigate burnout risk in public and private workplaces - Giulio Perrotta; Antonio Marciano; Gianfranco Fabiano (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
Starting from the general concept of "burnout", thus describing the lack of energy, fatigue, and unproductivity at work that a person develops in the workplace, the present paper defines the specific characteristics of the syndrome and related contexts and then proposes a new psychometric instrument (Perrotta-Marciano Burnout Risk Interview 1, BORI-1), in the interview version, capable of assessing and graduating the risk of the same, to intervene promptly in borderline situations that could degenerate into injurious and self-injurious acts. The interview aims to analyze the risk of burnout in individuals who work in both the private and public sectors and who for reasons of service may be put under pressure, even if they have passed the medical and psychiatric examination. It is therefore proposed as a tool for investigation, prevention, and clinical evaluation of burnout syndrome in its clinical signs, thus bridging the critical issues noted in the current psychometric instruments dedicated to the subject under consideration.